By the numbers: the construction industry in Canada from 1986 to 2016. (1st October 2020) - Haan, Michael; Hewitt, Christopher; Chuatico, Georgina
ABSTRACT: Construction is an important employer in all developed countries, which bolsters the local and global economy. The construction industry is responsible for creating structure that improve productivity and quality of life not only in Canada but also in other developed and developing countries. Although considerable research exists on important facets of the industry (including education, skills and training; precarious work; migration and labour mobility; gender, working-time and work-life balance), few studies look at how the labour force has changed over time. In this paper we model the factors that predict participation in the Canadian construction industry in 1986 and 2016, and document the changes between these two points in time. We find broad similarities between the sociodemographic characteristics of workers in 1986 and 2016, and large changes in the source regions of these workers. We also find different geographical mobility patterns between 1986 and 2016, and discuss the implications of these changes for both the industry itself, and the workers and families that derive their livelihoods from construction work.